Cognitive Dissonance Equilibrium: Local Product Stigma in the "Filosofi Pete" Ad Narrative Flow - Triyudanto, Arya; Dabukke, Fatrica Ivana; Marta, Rustono Farady; Panggabean, Hana; Wang, Changsong (Mediator: Jurnal Komunikasi, 2024)
Following the 1998 reform in Indonesia, advertising has undergone significant expansion, leveraging enhanced communication accessibility and media proliferation to shape public perceptions of promoted goods. Presently, media channels are inundated with commercial campaigns showcasing both domestic and international products. Within this landscape, Tokopedia, a key player in the e-commerce sector, employs diverse media platforms such as YouTube to engage consumers amid intensifying market rivalry. This study delves into Tokopedia's approach via the "Filosofi Pete" advertisement, exploring its endeavors to combat stereotypes surrounding local products. Drawing parallels between domestic goods and petai a culturally stigmatized item the research highlights the heightened stigma amid globalization, where foreign products often enjoy elevated prestige and perceived quality standards. Through the lens of cognitive dissonance theory and Todorov's narrative analysis, the analysis reveals Tokopedia's strategic narrative framework aimed at reshaping perceptions towards local products. By dissecting the advertisement's storyline, narrative structure, and visual elements, the study unveils Tokopedia's nuanced tactics for challenging entrenched biases. Through compelling storytelling and visual imagery, Tokopedia endeavors to reframe the discourse around local products, fostering a more favorable consumer outlook. This research sheds light on the intricate interplay between advertising strategies, cultural perceptions, and consumer behavior, offering insights into how brands navigate evolving market dynamics to carve out a competitive edge.